2021
DOI: 10.1093/eurpub/ckab134
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on the effects of previous stillbirth or abortion on subsequent pregnancies and infants

Abstract: Background This study was conducted to assess the effects of stillbirth and abortion on the health of the subsequent newborns. Methods A prospective cohort study was implemented. The data were collected from January 2015 to August 2019. The study participants were selected using the simple random sampling technique. The data were collected using interviewing the pregnant mothers, reviewing medical charts, analyzing the blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…History of abortion in this study demonstrated statistical significance as predictor of perinatal mortality. The finding is consistent with a study done in Ethiopia on the effects of previous stillbirth or abortion on subsequent pregnancies and infants increased the risk of infections (38), which increase the risk of perinatal mortality (39). In furtherance to this, we also found that having a history of stillbirth had five times higher risk of experiencing perinatal mortality compared to those who had never.…”
Section: Discussionsupporting
confidence: 92%
“…History of abortion in this study demonstrated statistical significance as predictor of perinatal mortality. The finding is consistent with a study done in Ethiopia on the effects of previous stillbirth or abortion on subsequent pregnancies and infants increased the risk of infections (38), which increase the risk of perinatal mortality (39). In furtherance to this, we also found that having a history of stillbirth had five times higher risk of experiencing perinatal mortality compared to those who had never.…”
Section: Discussionsupporting
confidence: 92%
“…The occurrence of preeclampsia during pregnancy seems to be one of the major factors significantly increasing the risk of miscarriages and stillbirths. According to recent reports, abovementioned factors contribute to decrease newborn weight [ 43 , 44 , 45 ]. Furthermore, targeted and increased surveillance should also be provided for women with a past history of miscarriages, abortions, or stillbirths.…”
Section: Methodsmentioning
confidence: 99%